2017
DOI: 10.1038/s41598-017-10423-w
|View full text |Cite
|
Sign up to set email alerts
|

Cervical nodal volume for prognostication and risk stratification of patients with nasopharyngeal carcinoma, and implications on the TNM-staging system

Abstract: We aim to evaluate the quantitative parameters of 18F-FDG PET/CT (metabolic parameters) and MRI (morphologic parameters) for prognostication and risk stratification in nasopharyngeal carcinoma (NPC). 200 (147 males, aged 50 ± 13 years-old, mean ± S.D.) newly diagnosed patients with NPC (TxNxM0) were prospectively recruited. Primary tumor and nodal lesions were identified and segmented for both morphologic (volume, VOL) and metabolic (SUV and MTV) quantification. Independent predictive factors for recurrence fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Chen et al demonstrated that the 5-year OS is reduced for patients with a large tumor volume (>50 ml), which is almost equal to that of T4 (2). Yuan et al found that morphologic nodal volume is an important factor in prognostication and risk stratification in NPC (3). Based on our study, we suggest that a larger tumor and cervical nodal volume are significantly associated with a poor survival rate.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Chen et al demonstrated that the 5-year OS is reduced for patients with a large tumor volume (>50 ml), which is almost equal to that of T4 (2). Yuan et al found that morphologic nodal volume is an important factor in prognostication and risk stratification in NPC (3). Based on our study, we suggest that a larger tumor and cervical nodal volume are significantly associated with a poor survival rate.…”
Section: Discussionsupporting
confidence: 69%
“…Combined chemotherapy and radiotherapy have been the current standard of treatment for NPC. Overall prognosis has furtherly improved in recent years (1)(2)(3). At present, the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) TNM staging system is used widely to predict prognosis for NPC.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to head and neck, lung, and esophageal cancers, where large LN volume negatively impact survival. 12,13,21 Interestingly, when substrati ed by pathologic response outcomes, the large axillary LN group with full or nodal PCR showed better RFS. This was not the case for the small axillary LN group.…”
Section: Discussionmentioning
confidence: 99%
“…Although LN involvement by pathology has been associated with poor RFS in breast and other cancers, the contribution of axillary LN volume alone as well as its association with PCR, and receptor status in determining RFS in breast cancer has not been adequately investigated. 12,13 This study sought to examine the contribution of axillary LN volume on RFS in breast cancer patients with sub-strati cation by molecular subtypes, and full or nodal PCR. We tested the hypothesis that large pre-treatment axillary LN volume is associated with poor RFS in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the N category, nodal volume was better at determining regional control for patients with NPC 77 . On the other hand, Yuan et al identified 18 cc to be the optimal cut‐off value for nodal volume based on both PET and MRI, 78 and proposed a new classification system in which N1 is nodal volume smaller than 18 cc with retropharyngeal nodes (regardless of laterality) and/or unilateral neck nodes, N2 is nodal volume smaller than 18 cc with bilateral neck nodes, and N3 is nodal volume ≥18 cc regardless of laterality. A similar cut‐off value of 20 cc was observed in a large data intelligence platform consisting of 1500 node‐positive NPC patients 79 …”
Section: Nodal Features That Influence Prognosismentioning
confidence: 99%